Pengembangan Modal Sosial dalam Penanggulangan Daerah Tertinggal di Kabupaten Pelalawan - Sujianto, Sujianto (Jurnal Ilmu Administrasi Negara, 2009)
Public administration reform was reinforced social capital in public. He have been able topenetrating power which centralistic. Besides also out for social capital got out of poorness depen-dence from various the progresses in this time. Factor pushing growing of social capital at publicPelalawan, 1) feel togetherness, 2) existence of desire and purpose of same, 3) flavor don’t gettingattention. 4) wish to advance. Research used have the character of method qualitative and datacollected with depth interview. Taking respondent with method purposive sampling. Data analysisdone by field with the phenomenon verification. Social capital which meant here is social rapportand norm which an in public social structure capable to coordinated action in reaching purpose ofwith. Result of study showed Sub-Province Pelalawan hardly kondusif for increasing viable qualityof live passed effort prosperity (economic unit) based on local strength. But that way, still berequired role of government for giving economic protection and give service of public in responsible.